Depressive symptoms and quality of life in people with a diagnosis of schizophrenia: An exploratory study of the potential mediating role of health‐promoting lifestyles. Issue 4 (20th April 2020) - Chang, Chia‐Chi; Beckstead, Jason W.; Lo, Su‐Chen; Yang, Chiu‐Yueh
Abstract: Purpose: To examine health‐promoting lifestyles mediates the relationship between depressive symptoms and quality of life (QOL) in people with schizophrenia. Design and Methods: A cross‐sectional exploratory study design was conducted. Two‐hundred and seventy‐three participants were administered demographic data, health‐promoting lifestyle profile, Beck Depression Inventory II, and World Health Organization Quality of Life‐BREF. The Hayes PROCESS macro was employed to analyze data. Findings: The results showed self‐actualization fully mediated the environmental domain of QOL, physical health, psychological health, and social relationships domains were partial mediation. Practice Implications: This study recommends that professionals reinforce persons' self‐actualization when the QOL is affected by depressive symptoms in people with schizophrenia.